Synthesis of quinoline-based NNN-pincer nickel(II) complexes: a robust and improved catalyst system for C–H bond alkylation of azoles with alkyl halides - Patel, Ulhas N.; Pandey, Dilip K.; Gonnade, Rajesh G.; Punji, Benudhar (Organometallics, 2016)
The quinoline-based pincer nickel(II) complexes κN,κN,κN-{R2N-C6H4-(μ-N)-C9H6N}NiX ((R2NNNQ)NiCl: R = Me, 2a; R = Et, 2b) were synthesized by the reaction of the ligand precursors (R2NNNQ)H (R = Me, 1a; R = Et, 1b) with (DME)NiCl2 in the presence of Et3N. Similarly, the pincer nickel(II) derivatives (R2NNNQ)NiX (R = Me, X = Br, 3a; R = Et, X = Br, 3b; R = Me, X = OAc, 4a) were obtained by treatment of the ligands (R2NNNQ)H with the nickel precursor (THF)2NiBr2 or Ni(OAc)2. All of these complexes were characterized by 1H and 13C NMR spectroscopy as well as by elemental analysis. Further, the molecular structures of 2a and 3a,b were elucidated by X-ray crystallography. Complex 2a is found to be an efficient catalyst for the direct C–H bond alkylation of substituted benzothiazoles and oxazoles with various unactivated alkyl halides containing β-hydrogens under mild reaction conditions. The catalyst 2a is very robust and was recycled and reused five times for the alkylation reaction without a decrease in its catalytic activity. Preliminary studies reveal that the catalyst 2a acts as an active catalyst and the alkylation reaction appears to operate via a radical pathway.

Scope and mechanistic aspect of nickel-catalyzed alkenylation of benzothiazoles and related azoles with styryl bromides - Patel, Ulhas N.; Jagtap, Rahul A.; Punji, Benudhar (Organometallics, 2019)
Alkenylation of benzothiazoles and related azoles with alkenyl bromides is achieved employing the well-defined and air-stable nickel complexes, (bpy)NiBr2 and [Ni(bpy)(3)] [NiBr4], as catalysts. Numerous electronically distinct alkenyl bromides efficiently coupled with substituted benzothiazoles, oxazoles, and benzimidazoles under the catalytic conditions to afford 2-alkenylated azoles. An extensive mechanistic study of the alkenylation of benzothiazole using (bpy)NiBr2 highlights a single-electron transfer process for the reaction involving the two-step one-electron oxidative addition of alkenyl bromide. The substrate benzothiazole plays a significant and diverse role in the reaction, and C-H bond cleavage is reversible in nature. Detailed kinetic analysis and control reactivity studies are indicative of a Ni(I)/Ni(III) pathway for the alkenylation comprising the rate-influencing reductive elimination step.